Characterization, structural study, Hirshfeld surface, vibrational properties and thermal analysis of a supramolecular hybrid compound: (C8H14N2)4·(TeBr6)3·2(Br) - Marwa Mhiri; Sergiu Shova; Mohamed Boujelbene (Results in Chemistry)
A novel supramolecular hybrid compound, (C8H14N2)4·(TeBr6)3·2(Br), was synthesized at room temperature through slow evaporation and thoroughly characterized. Single-crystal X-ray diffraction analysis revealed its monoclinic structure (space group C2/c), with the crystal stabilized by NH…Br hydrogen bonds, anion…π+ and π…π interactions. Hirshfeld surface analysis quantified the intermolecular interactions, highlighting H…Br as the most dominant (55.7 %). Vibrational properties analyzed using FT-IR and Raman spectroscopy confirmed the functional groups of both organic and inorganic components, while thermal analysis demonstrated stability up to 100 °C. Preliminary insights into its structural features, such as the presence of [TeBr6]2− units and π interactions, suggest potential catalytic activity alongside optoelectronic and dielectric applications, warranting further investigation.